The Influence of Brand Ambassadors on Tokopedia Buyer Interest in View from the Islamic Economic Consumption Theory - Yelpi Hertina; Wifqo Arova Syams (Sharia Economic and Management Business Journal (SEMBJ), 2023)
The aim of this research is first, to find out the influence of the Tokopedia brand ambassador among Bengkulu Kpopers. Second, find out buyers' interest in the Tokopedia application. This research is associative quantitative research, namely research that explains the influence of Brand Ambassadors on Tokopedia buyer interest in terms of Islamic Economic consumption theory. Based on the research results, it was concluded that the influence of Brand Ambassadors on Tokopedia buyer interest was reviewed from the Islamic Economics consumption theory. The results of hypothesis testing obtained a significance figure of 0.063. This shows that there is a significant relationship in this hypothesis test because the significance number is > 0.05 so that Ha which states that the use of Brand Ambassador has a positive effect on the interest of Tokopedia buyers in terms of Islamic economic consumption theory is accepted and H0 is rejected, meaning there is no influence on the use of the Brand. Ambassador (X) regarding the interest of Tokopedia buyers in terms of Islamic economic consumption theory (Y).